Playing against the house: the dramatic world of an undercover union organizer - Walsh, James D. (Scribner, 2016)
"Fascinating and groundbreaking: a talented young journalist goes undercover to work as a casino labor-union organizer in Florida in this rare, smart look at the ongoing struggle between the haves and the have-nots. Salting is a simple concept--get hired at a non-union company, do the job you were hired to do, and, with the help of organizers on the outside, unionize your coworkers from the inside. James Walsh spent almost three years as a "salt" in two casinos in South Florida, working as a buffet server and a bartender. Neither his employers at the casinos nor the union knew about Walsh's intentions to write about his experience. Now he reveals little-known truths about how unions fight to organize workers in the service industries, the vigorous corporate opposition against them, and how workers are caught in the battle. During his time as an undercover worker, Walsh witnessed the oddities of casino culture, the cultish nature of labor organizing, and surprising details of service industry employment. His revelations show the ferocious conflict between large service corporations and their hourly wage employees, who are hanging onto economic survival by their fingernails. The hotel and service union Walsh worked with employs young, college-educated activists and learning how salts use their skills to great success or failure is riveting. Walsh transports us directly to the hot, humid backroom of the Miami casino and shows how it feels to be grilled by a union organizer as to whether you have enough grit for the job. A clear-eyed and fascinating portrait of labor-organizing, Playing Against the House explores the trials of day-to-day life for the working poor to its effects on the middle class and the face of twenty-first century union busting in unprecedented detail."